Adiponectin Receptor Agonist, AdipoRon, Causes Vasorelaxation Predominantly Via a Direct Smooth Muscle Action. (April 2016) - Hong, Kwangseok; Lee, Sewon; Li, Rong; Yang, Yan; Tanner, Miles A.; Wu, Jianbo; Hill, Michael A.
Abstract: Objective: AdipoRon, an adiponectin receptor agonist, was recently proposed for treating insulin resistance and hyperglycemia. As adiponectin is vasoprotective via NO‐mediated signaling, it was hypothesized that adipoRon similarly exerts potentially beneficial vasodilator effects. We therefore examined if adipoRon induces vasorelaxation and via what contributing mechanisms. Methods: Vascular function was assessed in skeletal muscle arteries from rats and cerebral/coronary arteries from mice using pressure and wire myography. Results: Using qPCR, mRNA for adiponectin receptors was demonstrated in skeletal muscle, cerebral and coronary arteries. AdipoRon‐caused vasorelaxation was not abolished by compound C (10 μ M; AMPK inhibitor). Inhibition of endothelium‐dependent relaxation with combinations ofl ‐NAME/indomethacin/apamin/TRAM‐34 only slightly reduced adipoRon‐mediated vasorelaxation in cerebral and coronary arteries. EC‐denuded cremaster arteries showed similar relaxant responses to adipoRon as in intact vessels, suggesting adipoRon directly impacts VSMCs. K + currents measured in VSMCs isolated from mouse basilar and LAD arteries were not altered by adiopRon. In cremaster arteries, adipoRon induced vasorelaxation without a marked decrease in VSMC [Ca 2+ ]i . Adiponectin, itself, caused vasodilation in intact cremaster arteries while failing to cause significant dilation in EC‐denuded arteries, consistent with endothelium dependency of adiponectin. Conclusions: AdipoRon exerts vasodilation by mechanisms distinct to adiponectin. The dominant mechanism for adipoRon‐induced vasorelaxation occurs independently of endothelium‐dependent relaxing factors, AMPK activation, K + efflux‐mediated hyperpolarization and reductions in cytosolic [Ca 2+ ]i .